Christianity, patriotism, and nationhood : the England of G.K. Chesterton - Stapleton, Julia (Lexington Books, 2009)
This study links the concepts of patriotism, Christianity, and English national identity in the journalistic writings of G.K. Chesterton. It is the first work on Chesterton to explore in full the English attachments that were central to his political and spiritual persona, and their roots in a wider movement of English national consciousness in the early-twentieth century.